Remittance outflow, financial development and macroeconomic indicators: evidence from the UK - Ololade Periola; Monsurat Foluke Salami (Future Business Journal)
Abstract Remittances have become a significant component of international capital flows, with millions of migrants sending billions of dollars back to their home countries annually. However, the way these outflows affect macroeconomic variables has not received sufficient attention in the literature, especially in the context of varying levels of financial development. Using time series data from 1987 to 2022 for the United Kingdom, this study examines the macroeconomic effects of remittance outflows and financial development. Our baseline estimation using the Autoregressive Distributed Lag model reveals heterogeneous impacts, as remittance outflows adversely affect economic growth but improve exchange rates. We find remittances do not have a significant effect on inflation or bank rates. The moderating effect of financial development analysis reveals a similar outcome. Our results suggest governments should consider stimulus policies that support investment in productive sectors to improve macroeconomic indicators and facilitate financial inclusion to enhance the adoption of growth strategies that promote remittances.